Seismotectonic, rupture process, and earthquake-hazard aspects of the 2003 December 26 Bam, Iran, earthquake - Jackson, J; Bouchon, M; Fielding, E; Funning, G; Ghorashi, M; Hatzfeld, D; Nazari, H; Parsons, B; Priestley, K; Talebian, M; Tatar, M; Walker, R; et al. (2006)
The catastrophic 2003 Mw 6.6 Bam earthquake in southern Iran attracted much attention, and has been studied with an abundance of observations from synthetic aperture radar, teleseismic seismology, aftershock studies, strong ground motion, geomorphology, remote sensing and surface field work. Many reports have focused on the details of one or other data type, producing interpretations that either conflict with other data or leave questions unanswered. This paper is an attempt to look at all the available data types together, to produce a coherent picture of the coseismic faulting in 2003 and to examine its consequences for active tectonics and continuing seismic hazard in the region. We conclude that more than 80 per cent of the moment release in the main shock occurred on a near-vertical right-lateral strike-slip fault extending from the city of Bam southwards for about 15 km, with slip of up to 2 m but mostly restricted to the depth range 2-7 km. Analysis of the strong ground motion record at Bam is consistent with this view, and indicates that the extreme damage in the city can be attributed, at least in part, to the enhancement of ground motion in Bam because of its position at the end of the northward-propagating rupture. Little of the slip in the main shock reached the Earth's surface and, more importantly, aftershocks reveal that ∼12 km vertical extent of a deeper part of the fault system remained unruptured beneath the coseismic rupture plane, at depths of 8-20 km. This may represent a substantial remaining seismic hazard to the reconstructed city of Bam. We believe that some oblique-reverse slip (up to 2 m, and less than 20 per cent of the released seismic moment) occurred at a restricted depth of 5-7 km on a blind west-dipping fault that projects to the surface at the Bam-Baravat escarpment, an asymmetric anticline ridge that is the most prominent geomorphological feature in the area. This fault did not rupture significantly at shallow levels in 2003, and it may also represent a continuing seismic hazard. Widespread distributed surface ruptures north of the city are apparently unrelated to substantial slip at depth, and may be the result of enhanced ground motion related to northward propagation of the rupture. The faulting at Bam may be in the early stages of a spatial separation ('partitioning') between the reverse and strike-slip components of an oblique convergence across the zone. Such a separation is common on the continents, though in this case the slip vectors between the two faults differ only by ∼20° as a substantial strike-slip component remains on the oblique-reverse fault. The Bam earthquake is one in a series of large earthquakes involving faulting along the western edge of the Lut desert. In addition to the unruptured parts of the faults near Bam itself, continuing and substantial hazard is represented by unruptured neighbouring faults, particularly blind thrusts along the Jebel Barez mountains to the south and strike-slip faulting at Sarvestan to the west. © 2006 The Authors Journal compilation © 2006 RAS.